Perancangan Interior Café Co-Working Space di Surabaya - Wijaya, Kenny Ray; Honggowidjaja, Stephanus Pantja; Rizqy, Muhammad Taufan (Intra, 2019)
Co-Working Space Café is a place designed for visitors that come to the cafe could do their work or hanging out with their friends. So the visitors who come can increase their productivity and also be able to gather with their friends comfortably. The concept of this café is "coffee philosophy" which means prioritizing all parts of the coffee philosophy and maximizing the comfort that visitors will experience, because coffee has its own unique taste, and visitors can enjoy various dishes with coffee as the main ingredients which will give a distinctive coffee aroma to helped visitors to get inspiration and supported with interior dominant with brown color to give a comfortable and clean feeling.